FAKTOR-FAKTOR YANG MEMPENGARUHI CASH HOLDING PADA PERUSAHAAN MANUFAKTUR TAHUN 2019-2021 - Bahusatya, Narauttama; Nariman, Augustpaosa (Fakultas Ekonomi, Universitas Tarumanagara, 2025)
This research has a form to find out and get empiirical evidence of the effect of leverage, growth opportunity and net working capital on cash holdings in manufacturing companies in the basic materials sector and healthcare sector. Sampling in this research using purposive sampling technique. The data used were 66 companies with a total of 198 sample data. Data processing in this research used IBM SPSS version 29. The result of this research indicate that leverage and net working capital have a negative signifficant effect on cash holding, while growth opportunity has a negative insignificant on cash holding.